Contrasting elevational patterns and underlying drivers of stream bacteria and fungi at the regional scale on the Tibetan Plateau. Issue 6 (28th April 2022) - Liu, Jiawen; Zhao, Wenqian; Ren, Minglei; Liu, Yongqin; Xu, Yan; Wang, Jianjun
Abstract: Elevational gradients are the focus of development and evaluation of general theories on biodiversity. However, elevational studies of microorganisms and the underlying mechanisms remain understudied, especially at regional scales. Here, we examined stream bacterial and fungal communities along an elevational gradient of 990–4600 m with a geographic distance up to 500 km in the southeastern Tibetan Plateau and further analyzed their elevational patterns and drivers of three biodiversity indicators, including species richness, ecological uniqueness, and community composition. Bacteria and fungi showed distinct elevational trends in species richness and consistently decreasing patterns in their ecological uniqueness. The distance–decay relationships were concordant for the two microbial groups, while fungi showed higher dissimilarity and a lower turnover rate. Interestingly, bacterial and fungal compositions substantially differed between the elevations below and above 3000 m. Climate predictors, such as the mean annual temperature and precipitation seasonality, had greater effects than local environment drivers. Notably, fungal diversity was mainly influenced by climate, while bacterial diversity was explained by the shared contributions of climate and local factors. Collectively, these findings revealed the elevational patterns of stream microbial biodiversity across mountains on a large spatial scale and highlight their underlying response mechanisms to environmental predictors. Abstract : This research reveal the elevational patterns and driving factors of diversity and community composition of bacteria and fungi ranging from 990 to 4600 m a.s.l. across 500 km on the Tibetan Plateau.